2012
DOI: 10.1007/s00603-011-0218-6
|View full text |Cite
|
Sign up to set email alerts
|

Case Histories of Four Extremely Intense Rockbursts in Deep Tunnels

Abstract: In the process of excavating seven parallel tunnels at the Jinping II Hydropower Station, several extremely intense rockbursts occurred, killing and injuring construction workers and damaging several sets of equipment. Based on the characteristics and mechanisms of these rockbursts, four typical events were selected and their temporal and spatial characteristics were here described in detail. The geological conditions revealed after the rockbursts were surveyed carefully. The responses of support elements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(83 citation statements)
references
References 8 publications
6
77
0
Order By: Relevance
“…4 shows other tunnel failures induced by intense strainbursts. Based on the characteristics and mechanisms of these strainbursts, four typical events were selected, and their temporal and spatial characteristics were described by Zhang et al (2012b). Other details about the rockbursts in the deep tunnels of the Jinping II project can be found in related references (Chen et al 2015;Li et al 2012a).…”
Section: Strainburst Characteristic Analysis For the Jinping II Projectmentioning
confidence: 99%
See 2 more Smart Citations
“…4 shows other tunnel failures induced by intense strainbursts. Based on the characteristics and mechanisms of these strainbursts, four typical events were selected, and their temporal and spatial characteristics were described by Zhang et al (2012b). Other details about the rockbursts in the deep tunnels of the Jinping II project can be found in related references (Chen et al 2015;Li et al 2012a).…”
Section: Strainburst Characteristic Analysis For the Jinping II Projectmentioning
confidence: 99%
“…Location and layout of tunnels in the Jinping II hydropower station (reproduced fromLi et al 2011Li et al , 2012aZhang et al 2012b;Xu et al 2011) N. W.Xu et al …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it was found that pillar bursts occurred after blasting in some deep gold mines in South Africa (Malan 1999). Some extremely intense rockbursts occurred when actually there were no excavation activities at the tunnel face at Jinping II hydropower station in China (Li et al 2012;Zhang et al 2012). For instance, 38 delayed rockbursts were recorded and the longest delayed rockburst was recorded 163 d after the excavation .…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…During the tunneling of the headrace tunnels at the Jinping II hydropower station, a large amount of intense rockbursts occurred not only causing casualties and equipment troubles, but also resulting in many problems like project delays [10]. As is well known, rockbursts have extremely complicated evolution mechanisms [11][12][13].…”
Section: Introductionmentioning
confidence: 99%